Digital Marketing Strategies for Consumer Websites on the Ecuador/Colombia Border - Arias-Flores, Hugo (2023)
The use of web pages as a means of communication with customers has transformed online consumer interaction. The opportunities offered by technology and the challenges it brings to the marketplace are different for online consumers, as strategies to meet their needs must be identified based on their behavior on the website. In this context, the study seeks to determine if the websites of two financial institutions located on the border of Ecuador and Colombia present significant differences for clients, both in their presentation and in their ease of access. Through a survey (N = 96) the digital marketing strategies used were evaluated. The results show that a higher percentage (68.8%) accesses the websites through mobile devices and the age range is concentrated in the 25 to 34-year-old segment. However, the statistical tests show that there are no significant differences in the two websites analyzed, this shows that customers do not find a difference between the two institutions, which could reduce the perceived value and customer satisfaction.